Psychoeducation on the Role of Parents in Building Children's Creativity Through Fantasy Play - Maurilla, Talitha; Soetikno, Naomi; Iriani Roesmala Dewi, Fransisca (ARSY : Jurnal Aplikasi Riset kepada Masyarakat, 2025)
Creativity is an essential skill for children to navigate developmental challenges and the demands of the 21st century. However, many parents are still unfamiliar with practical ways to stimulate this ability through daily interactions. This community service program (PKM) aimed to enhance parents’ understanding and skills in fostering children’s creativity through fantasy play and supportive parenting practices. The program was conducted at RPTRA Rawa Indah and collaborated with PAUD X, Jakarta, through an interactive seminar integrating developmental psychology theories, recent empirical findings, demonstrations of fantasy play activities, and reflective discussions on parental roles. The implementation consisted of preparation, material development, event dissemination, and on-site seminar delivery. The results indicate increased parental understanding of fantasy play and its contribution to children’s creativity. Participants also reported greater readiness to implement imaginative activities and supportive parenting approaches at home. Overall, this PKM program contributed to strengthening evidence-based parenting literacy and enhancing collaboration between early childhood institutions and parents in supporting optimal child development.